Metaverse Prototype Designing of Thai Film Archive (Public Organization) for an Immersive Experience - Yuttana Suntivong; Khemmapat Patcharawit (Asian Creative Architecture, Art and Design : ACAAD, 2024)
This research focuses on the design of a Metaverse Prototype Thai Film Archive (Public Organization) to study immersive experiences. The aims were to: 1) examine design concepts and technologies for digital immersion, 2) create and showcase these designs in the Metaverse cinema, and 3) evaluate the results and formulate knowledge for virtual exhibition design using qualitative research methods, including prototype testing with participant interviews to assess satisfaction. The design principles consisted of architectural, exhibition, and user experience concepts, leading to a virtual world creation process involving 3D structural modeling, interactive functionalities, and exhibition layout before prototype testing. The evaluation included tests by ten participants and group discussions on overall experience, cinema content value, Metaverse design, and educational enhancement in museums. The design evaluation indicated a 70% positive overall experience, with half of the users finding stable usability. However, significant viewing barriers were identified, with a high need for operational instructions and navigational aids. Content understanding and Metaverse interaction were perceived positively, and the educational aspect was highly valued. The study concludes that while the overall experience was good, technology limitations (as of 2023) and interaction challenges require ongoing refinement to improve stability and usability, although the educational value was affirmed as strong.
Keywords: Virtual Reality Applications and Impacts